Optimism and Mindfulness Are Strongly Linked to Adolescent Psychological Well-Being: Optimisme dan Kesadaran Sangat Terkait dengan Kesejahteraan Psikologis Remaja - Maryam, Effy Wardati; Chusnah, Asmaul (Psikologia : Jurnal Psikologi, 2025)
Psychological well-being is an important thing that teenagers need to have in order to face the demands and fulfill their developmental tasks. The aim of this research is to determine the relationship between optimism and mindfulness and psychological well-being in junior high school teenagers in Sidoarjo Regency. Data was collected through distributing questionnaires using a Likert scale model with three psychological scales, namely psychological well-being, optimism and mindfulness. The population in this study was junior high school teenagers in Sidoarjo Regency totaling 33.191 students. Based on Issac and Michael's table with an error rate of 5%, up to 380 students were obtained using the accidental technique. The data analysis used is multiple linear regression. The research results show that: 1) there is a positive relationship between optimism and psychological well-being (R=0.860, p=0.000<0.05). 2) there is a positive relationship between mindfulness and psychological well-being (R=0.822, p=0.000<0.05). 3) there is a positive relationship between optimism and mindfulness and psychological well-being (p=0.000<0.05) with a coefficient of determination (R Square) value of 0.821, which means that optimism and mindfulness simultaneously make an effective contribution to psychological well-being of 82.1% . Highlights: Strong Positive Relationship – Optimism and mindfulness both have a significant positive correlation with psychological well-being in junior high school students. High Contribution Rate – Optimism and mindfulness together account for 82.1% of the variation in psychological well-being, highlighting their crucial role. Scientific Validation – The study, using multiple linear regression on 380 students, confirms that fostering optimism and mindfulness can enhance teenagers' psychological well-being. Keywords: Psychological Well-Being, Mindfulness, Optimism